Acute Myeloid Leukemia Presenting as Acute Bulbar Palsy (Bangladesh Journal of Medical Science, 2014)
Myeloid Sarcoma1 (also termed as chloroma, granulocytic sarcoma, extra medullary myeloid tumor) is a rare extra medullary tumor composed of immature myeloid cells (myeloblast)2. It is usually associated with leukemia or other myeloproliferative disorder. Myeloid Sarcoma in the central nervous system, around the brain stem is the commonest site of presentation and require high suspicion for diagnosis. We report a forty years male patient with history of dysphagia, dysphonia for last two months. MRI showed chloromas around the brain stem. Laboratory investigations revealed the presence of AML. This is a rare case of Myeloid Sarcoma around the brain stem in a patient of AML. DOI: http://dx.doi.org/10.3329/bjms.v13i4.16056 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.481-483